Kasabach-Merritt syndrome: clinical vs. surgical treatment - Moura, Regina [UNESP]; Sobreira, Marcone Lima [UNESP]; Bertanha, Matheus [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Silva, Maria Madalena [UNESP]; Pereira, Lied [UNESP]; Takegawa, Bonifácio Katsunori [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2014)
Kassabach-Merritt syndrome is a combination of capillary hemangioma and thrombocytopenia that predisposes to bleeding with petechiae, ecchymosis and spontaneous bruising. Treatment is generally started with corticosteroids, interferon alpha or chemotherapy. We present the case of a child (aged 1 year and 9 months) with a giant hemangioma, from the root of the thigh to the knee, and thrombocytopenia. Treatment was started with corticosteroids, without improvement, and then intra-tumor and cutaneous bleeding appeared spontaneously. The patient’s clinical condition precluded prescription of vincristine and interferon and emergency tumor resection was conducted because of extreme thrombocytopenia and bleeding. The child then began to develop sepsis with hypotension and ischemia of remnant tissues. This case presented a therapeutic challenge, which is the subject of this article.

A síndrome de Kassabach-Merritt é uma associação de hemangioma capilar e trombocitopenia, que promove sangramentos com petéquias, equimoses e hematomas espontâneos. A conduta é tratar com corticoide, interferon alfa ou quimioterápicos. Apresentamos um caso de criança (com 1 ano e 9 meses anos de idade) com um hemangioma gigante desde a raiz da coxa até altura do joelho, e plaquetopenia. O tratamento foi iniciado com corticoterapia sem melhora do quadro, surgindo de forma espontânea pontos de sangramento intratumoral e cutâneo. Sem condições clínicas de receber vincristina e o interferon, foi feita a ressecção tumoral de urgência por extrema plaquetopenia e sangramento. A criança começou então a desenvolver um quadro séptico com hipotensão e isquemia do tecido residual. Diante deste quadro, configurou-se um desafio terapêutico que será objeto deste artigo.
Síndrome de Kasabach-Merritt: tratamento clínico versus cirúrgico
Keywords: Kasabach-Merritt syndrome; Amputation; Corticosteroids; Hemangioma; Síndrome de Kasabach-Merritt; Amputação; Corticoides; Hemangioma